Correlates of COVID-19 conspiracy theory beliefs in Japan: A cross-sectional study of 28,175 residents. - Yukihiro Sato; Ichiro Kawachi; Yasuaki Saijo; Eiji Yoshioka; Ken Osaka; Takahiro Tabuchi (PLoS ONE)
Background The COVID-19 pandemic was associated with an increase in conspiracy theories worldwide. However, in Japan, the prevalence of COVID-19 conspiracy beliefs has remained unclear. This study aimed to estimate the prevalence and correlates of COVID-19 conspiracy beliefs using a survey of 28,175 residents of Japan aged 16-81 years old. Methods A cross-sectional self-administered survey was conducted from September to October 2021. To assess the number of COVID-19 conspiracy beliefs, we used three questions from the Oxford Coronavirus Explanations, Attitudes, and Narratives Survey. Independent variables included general vaccine conspiracy beliefs, sociodemographic variables, information sources for COVID-19, trust in authorities, and fear of COVID-19. Results After applying sampling weights and imputation, the estimated prevalence of holding at least one COVID-19 conspiracy belief was 24.4%. From a linear regression model, several factors were independently associated with conspiracy beliefs. Notably, people with the lowest level of education (lower secondary school) endorsed fewer COVID-19 conspiracy beliefs (B -0.089, vs. upper secondary school). Furthermore, higher socioeconomic backgrounds-such as higher income, higher wealth, and regular employment-were associated with endorsing conspiracy beliefs. Only 37.3% of respondents trusted the government of Japan, but paradoxically, trust in the government was positively associated with conspiracy beliefs (B 0.175, vs. distrust). Conclusions COVID-19 conspiracy beliefs can be prevalent in about a quarter of the residents of Japan. Certain groups are more likely to endorse conspiracy beliefs, and targeting interventions towards these groups might be efficient in stemming the spread of conspiracy beliefs.